2015
DOI: 10.1002/ajh.23942
|View full text |Cite
|
Sign up to set email alerts
|

Bosutinib, a Lyn/Btk inhibiting tyrosine kinase inhibitor, is ineffective in advanced systemic mastocytosis

Abstract: a trend was seen for improved survival (P 5 0.08).Our goal is to improve the nationwide survival of myeloma patients. We have established a national registry of all myeloma patients to identify areas of intervention. A population-based survey showed no difference in causes of death among patients ineligible for HDT, who died within 30 days from diagnosis as compared to patients who died between 31 and 180 days. Patients who died within 30 days had higher LDH levels and lower levels of plasma albumin as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Given that approximately 90% of patients with advanced SM have a mutation in the KIT gene (mostly KIT D816V), tyrosine kinase inhibitors (TKI) have also been used recently; however, the clinical efficacy of most KIT-targeted TKIs has been disappointing. The KIT D816V mutation is resistant to imatinib, and despite in vitro activity against KIT D816V, dasatinib and nilotinib have shown limited activity in phase II trials in KIT D816V-mutated advanced SM [12][13][14][15][16][17][18]. Midostaurin, a multikinase inhibitor available on an investigational and compassionate-use basis, has shown promising results in patients with advanced SM in a phase II study [19].…”
Section: Introductionmentioning
confidence: 99%
“…Given that approximately 90% of patients with advanced SM have a mutation in the KIT gene (mostly KIT D816V), tyrosine kinase inhibitors (TKI) have also been used recently; however, the clinical efficacy of most KIT-targeted TKIs has been disappointing. The KIT D816V mutation is resistant to imatinib, and despite in vitro activity against KIT D816V, dasatinib and nilotinib have shown limited activity in phase II trials in KIT D816V-mutated advanced SM [12][13][14][15][16][17][18]. Midostaurin, a multikinase inhibitor available on an investigational and compassionate-use basis, has shown promising results in patients with advanced SM in a phase II study [19].…”
Section: Introductionmentioning
confidence: 99%
“…49 However, bosutinib is unable to induce any response in patients with AdvSM. 87 Treatment in advanced SM haematologica | 2016; 101 (10) 1137 Figure 2. Synthesis of the frequency of the various molecular defects found in AdvSM, which sums up all the advanced (AdvSM) SM patients (n=122) reported in the studies by Tefferi et al, 62 Wilson et al, 63 Traina et al, 61 Schwaab et al 64 and Hanssens et al 65 The frequency (%) of cases found positive for each genetic defect is represented in red, whereas the frequency of patients for whom the corresponding defect was not tested is represented in blue.…”
Section: Critical Intracellular Pro-oncogenic Pathways In Neoplastic mentioning
confidence: 99%
“…This observation positioned SFKs as attractive targets for the treatment of systemic mastocytosis. However, selective inhibition of the activity of SFKs alone, using an inhibitor such as bosutinib, has been shown to be ineffective as a stand-alone agent; their use in combination therapy may prove to be more valuable [ 111 ].…”
Section: Sfks In Mastocytosismentioning
confidence: 99%